[Digital] Visual Effects and Compositing - Gress, Jon (New Riders, 2014)
In this latest book in the critically-acclaimed [digital] series from New Riders you'll learn all of the techniques and skills that will take you from beginner to visual effects (VFX) professional in just one book. Seasoned visual effects producer Jon Gress has refined the teaching of the skills and techniques presented in this book for over a decade to distill them down to the most effective methodology, delivered in a way that's both fun and easy to understand while being state-of-the-art for industry professionals. You'll start with a solid understanding of the basics of visual effects and compositing, the fundamentals of bluescreen and greenscreen keying, 3D texturing, cloning, wire and rig removal, rotoscoping, 2D and 3D motion tracking, and matchmoving. And then experiment with a wide range of 2D, 2.5D and 3D visual effects, including 3D CGI, crowd replication, face replacements, faking shadows, reflections and Z depth, atmospheric, smoke, cloud and heat FX, sky replacements, day-for-night and digital 3D HUD FX. Building on this strong foundation of compositing and visual effects, you'll be prepared for the advanced section of the book which teach skills, such as 2D, 2.5D and 3D digital matte painting and projections, film colorization, particle systems, fluid and rigid body dynamics, full digital environments, digital destruction, advanced lighting and rendering techniques, stereoscopic 3D, 2D to 3D conversions, and expert 3D and Photoshop extraction and modeling techniques that can only be described as magic! Throughout the lessons, you'll glean insider advice on cutting edge methods that even experienced professionals will find amazing. You'll learn everything you need to know to begin working in the world of visual effects as an industry professional. {u2022} All the info you need to go from beginner to professional in one book {u2022} Easily accessible teaching style from an instructor who has helped launch the careers of some of the best-known Hollywood visual effects specialists {u2022} Includes companion graphics files and videos to follow along with the lessons.